2016
DOI: 10.5301/jbm.5000211
|View full text |Cite
|
Sign up to set email alerts
|

High Copy Number of Mitochondrial DNA Predicts Poor Prognosis in Patients with Advanced Stage Colon Cancer

Abstract: High mtDNA content is a potential effective factor of poor prognosis in patients with advanced stage colon cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 18 publications
2
25
0
Order By: Relevance
“…After a thorough review of titles and abstracts by two investigators independently, 394 studies were excluded and the full texts of remaining 26 references have also been artificial retrieved for further identification. Finally a total of 20 retrospective studies comprising 5413 patients were included in our study and 18 studies were used for analysis16171819202122252627282930313233343536. Among the included studies for analysis, there were 16 studies recruited Asian patients while 2 studies recruited Caucasian patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After a thorough review of titles and abstracts by two investigators independently, 394 studies were excluded and the full texts of remaining 26 references have also been artificial retrieved for further identification. Finally a total of 20 retrospective studies comprising 5413 patients were included in our study and 18 studies were used for analysis16171819202122252627282930313233343536. Among the included studies for analysis, there were 16 studies recruited Asian patients while 2 studies recruited Caucasian patients.…”
Section: Resultsmentioning
confidence: 99%
“…Among these factors, the qualitative and quantitative changes in nuclear or mitochondrial DNA have been frequently reported in human cancers262728293031, and the interplay between them may partly participate in the tumor-related process39. Previous studies have reported reduced levels of mtDNA transcripts and increased mtDNA copy number in brain and lung with ageing4041.…”
Section: Discussionmentioning
confidence: 99%
“…But it is known meanwhile that mtDNA content and OXPHOS activity do not always correspond well in tumor tissues and -more importantly- copy number studies sometimes did not even deliver homogenous results within a single entity. For example, in colorectal cancer one recent study observed a lower mtDNA copy number in colorectal carcinomas as compared to adenomas [95], while another publication described higher copy numbers in colorectal cancer tissues as compared to adjacent normal tissues and a positive association of high copy number with poor prognosis [96]. An increased mtDNA-level in gliomas was observed as compared to (not matched) normal brain tissues, high copy number being associated with better prognosis [97].…”
Section: Is Mtdna Copy Number Associated With Prognosis or General Camentioning
confidence: 99%
“…Wang et al supported that the mtDNA copy number increased in CRCs and it was a factor of poor prognosis [22]. The researches of Haja Mohideen et al suggested that mtDNA copy number both increased and decreased in CRCs and no association of the mtDNA copy number change with OS or DFS [23].…”
Section: Mtdna Copy Numbermentioning
confidence: 99%